2010
DOI: 10.1016/j.compscitech.2010.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable polyurethane composite scaffolds containing Bioglass® for bone tissue engineering

Abstract: polyurethane composite scaffolds containing Bioglass® for bone tissue engineering.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
89
0
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(95 citation statements)
references
References 80 publications
3
89
0
3
Order By: Relevance
“…However, the work by Srinivasan et al showed a decrease in porosity ratio by addition of more nano-bioglass [30]. Overall, the ideal porosity percentage can be defined by the final application and also when there is a compromise between mechanical and biological properties [34].…”
Section: Thermal Analysismentioning
confidence: 99%
“…However, the work by Srinivasan et al showed a decrease in porosity ratio by addition of more nano-bioglass [30]. Overall, the ideal porosity percentage can be defined by the final application and also when there is a compromise between mechanical and biological properties [34].…”
Section: Thermal Analysismentioning
confidence: 99%
“…20 Composite scaffolds containing polymers and bioactive inorganic materials have attracted growing attention for bone tissue regeneration. 21 Therefore, it can be suggested that the introduction of the bioactive material n-BD into PCL-PEG-PCL was a good method to prepare bioactive composite scaffolds for bone repair.…”
Section: Results and Discussion Composition And Structure Of N-bd Andmentioning
confidence: 99%
“…This could be explained by considerable structural changes connected with the reduction of chain lengths followed by eventual physical crosslinking of macromolecules after degradation [18,24].…”
Section: Resultsmentioning
confidence: 99%